Framing Research on Service - Möslein, Kathrin; Huff, Anne Sigismund (Research Methodology in Strategy and Management, vol.5, 2009)
Strategy researchers have given very little attention to services, even though they now dominate the gross domestic product of almost all countries. We encourage more research focused on service as the basic mode of generating revenue today, especially as the economic landscape is being restructured by recent financial crises. This chapter suggests a basic framework for services research and then outlines issues in three areas that are particularly important to customer-oriented service innovation: individuation, standardization, and export. Illustrative examples from Germany provide more specific contexts for considering the range of activity in this under-researched domain.
WiSo-Import:2015-04-20:2205